Sosialisasi Penyusunan E-Modul Interaktif Berbasis IT - Zuhra Meiliza; A.M, Muh. Inayah; M, Irmawati (Universitas Sulawesi Barat, 2023)
Socialization of the preparation of e-modules is an activity carried out with the aim of providing understanding to teachers in compiling interactive e-modules using IT. One IT application that can be used is the Canva application. The activity was carried out for 3 months starting April 10 – July 10 2023. The location of this activity was SDN No. 49 inp. Residence. Participants in the activity totaled 14 teachers. The team involved in implementing the activity was 3 lecturers and involved 5 PGSD students. The implementation of activities uses several stages including the formation of a Community Service Team (PKM), observation, committee meetings, activity implementation and activity evaluation. Based on the results of the activity evaluation using a questionnaire filled out by the participants it showed that there were significant differences before and after the activity. Before the activity, some of the participants were not able to operate the Canva application and had never made interactive e-modules, while after the activity, most of the participants were able to operate the Canva application in making interactive e-modules. The socialization of the preparation of interactive e-modules is expected to assist teachers in making teaching devices or materials that can be used during the learning process.